2017
DOI: 10.1155/2017/7238672
|View full text |Cite|
|
Sign up to set email alerts
|

Unilateral Aplasia versus Bilateral Aplasia of the Vertebral Artery: A Review of Associated Abnormalities

Abstract: Morphological characteristics of 108 cases of uni- and bilateral aplasia of the vertebral artery (VA) in reports or images of retrospective studies, including one recent case, published between 1967 and 2016 are analyzed. Incidence, gender, persistence of carotid-vertebrobasilar anastomosis (CVBA), associated with other vascular variants, and vascular pathology in each group of uni- and bilateral VA aplasia are mutually compared. Most of the cases of VA aplasia in ages 31 to 80 were discovered in USA, Japan, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…These studies have found a relationship with the occurrence of the left primitive trigeminal artery and the so-called intermediate communicating artery in cases of left vertebral artery agenesis. Specific symptoms have been associated with this entity, including headache, vertigo and weakness [6] . Aristeidis H et al.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found a relationship with the occurrence of the left primitive trigeminal artery and the so-called intermediate communicating artery in cases of left vertebral artery agenesis. Specific symptoms have been associated with this entity, including headache, vertigo and weakness [6] . Aristeidis H et al.…”
Section: Discussionmentioning
confidence: 99%
“…ere was no associated pathology in 17.80% of cases; however, there were 21 different pathological states in other cases, and among them the aneurysms of some cerebral arteries in 13.69% [24,31,42,52,53,58,61,62,67,71]. e authors have presented the morphofunctional status of blood vessels and stated the clinical importance in the cases of the absence of the VA [92], or the bilateral ICA [93], and the CCA in this manuscript; the next task will be a comparison of the cases with the le and the ones with the right ICA absence.…”
Section: Collateral Pathwaysmentioning
confidence: 99%
“…Although a headache was more common among them, it was also an initial symptom in other cases of vascular absence, such as the uni-or bilateral absence of the VA [92], or the bilateral absence of the ICA [93], as well as in many pathological disorders. A suspect pulsatile swelling in the neck caused by the cervical aortic arch, as a reason of/for the discovery of the CCA aplasia [6, 9, 33, 34, 36, 39, 67, 70, 73-75, 77, 81], may not always be related to it, as evidenced by Shepherd et al [37].…”
Section: Collateral Pathwaysmentioning
confidence: 99%
“…Arterial abnormalities, such as (total or segmental) aplasia [2][3][4]9], or fenestration [2,5,7,10,11] can be associated with some of the previously mentioned variations. However, both states of arteries could be with [10], or with no cerebral pathology [7,11].…”
Section: Introductionmentioning
confidence: 99%